Pengaruh Digitalisasi Al-Quran Terhadap Intensitas Pembacaan Al-Quran Pada Pelajar di Kota Bandung - Sultan Nazmi Chairul Islam; Andre Safrie Maulana; Helmi Nurapriliansyah; Muhammad Risdan Putra Setiawan (AR-RASYID : Jurnal Pendidikan Agama Islam, 2022)
The research conducted by the author aims to observe more broadly the impact of the emergence of various digital Al-Quran products as a product of digitalization in the field of religion. The impact in question is devoted to the intensity of the readings carried out and the usefulness obtained by the users. The research method used in this study is a qualitative descriptive analysis method. The questionnaire that has been made consists of several parts, namely, identity and questions. This questionnaire contains a total of 13 questions. This questionnaire consists of two types of questions, namely, fill-in questions (essays) and choice questions (yes/no. The data analysis of the survey results is processed by means of data collection, data sorting or filtering, data presentation, and data simplification. Then the data from the research analysis are summarized in the concept of and classified according to categories and poured in descriptive form and then the final conclusion is drawn. The results obtained are a decrease in the intensity of reading the Qur'an in respondents. In addition, overall the respondents prefer the conventional Al-Quran over the digital Al-Quran. This is reinforced by the preference for the conventional Al-Quran in several aspects such as the level of understanding in studying the Qur'an, the level of appreciation and practice of the Qur'an, and the level of increasing reading intensity. .Nevertheless, the majority respondents agree that the emergence of a digital Al-Quran can facilitate various aspects of life.